Justice and law in / for the Information Society - De Ortúzar, María Graciela; Olivera, Noemí; Proto, Araceli
This paper aims at contributing to the theoreticar discussion abaut palicies and laws that are required to achieve the Informatian Society (IS). There cannat be found a specific and systemic legal policy regarding the IS al/ over the world. Whereas selt regulation is being promoted from the Wortd Summit far Information Society (WSIS), it is not within the reach of those who are not able to, to predispose a legal situation in their own benefit. As a consequence, there is a great inequality between rieh and poor countries as regards the direction and priorities of the distribution and access to the Internet services and other benefits of the lS. For that reason, we hold that justice considerations cammit us to al/acate benefit according to needs. Our duty is to use an allocation criterion that not only does not discriminate in terms of irrelevant moral reasons, but foeuses on the real needs of the specific developing society as well. And so, we uphold that an integrated society demands general rules -laws- to set up the 1S legal trame, and they must be basad on ethics.
Keywords: Legal policies; Ethics; Law